1996
DOI: 10.1177/026921639601000307
|View full text |Cite
|
Sign up to set email alerts
|

The Provision of a Palliative Care Service in a Teaching Hospital and Subsequent Evaluation of That Service

Abstract: A survey at a large tertiary referral hospital showed that patients with cancer and HIV disease had poorly controlled symptoms. A palliative care service was introduced, employing a doctor and part-time pharmacist. The doctor was available to see and advise about terminally ill patients. With the pharmacists, an educational programme of meetings, teaching sessions and information leaflets was developed. One year after the introduction of the service a repeat survey all patients with cancer or HIV disease was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 19 publications
0
23
0
1
Order By: Relevance
“…48 The identification of evidence is also hampered by studies combining diagnosis groups. For example, one study 49 reported palliative care consultations in an acute care hospital where only 8.3% of patients had HIV disease, a second study of the benefits of symptom control by a hospital based palliative care consultant and pharmacist also had only 8% of patients with HIV, 50 and a third study of parenteral antibiotics in an inpatient palliative care unit reported 15% of patients having an underlying HIV diagnosis. 51 The potential for a selection bias in HIV palliative care evaluation was demonstrated in a study that found patients reported lower levels of pain, better insight, less anxiety, and fewer spiritual problems than in providers' assessments.…”
Section: Discussionmentioning
confidence: 99%
“…48 The identification of evidence is also hampered by studies combining diagnosis groups. For example, one study 49 reported palliative care consultations in an acute care hospital where only 8.3% of patients had HIV disease, a second study of the benefits of symptom control by a hospital based palliative care consultant and pharmacist also had only 8% of patients with HIV, 50 and a third study of parenteral antibiotics in an inpatient palliative care unit reported 15% of patients having an underlying HIV diagnosis. 51 The potential for a selection bias in HIV palliative care evaluation was demonstrated in a study that found patients reported lower levels of pain, better insight, less anxiety, and fewer spiritual problems than in providers' assessments.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the patients visited (91.4%) suffered from malignant diseases. Data before 2000 showed that a quarter of the patients, who were visited, suffered from AIDS [21]. Introduction of antiviral therapy regimes resulted in less necessity for palliative care in developed countries.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, studies on requests for professional consultation in the field of palliative care are also scarce. In much of the literature, consultation only appears as a side issue among support teams whose primary task was the direct provision of care to the patient and family [3,5,8,12,[17][18][19]. A few studies addressed purely advisory services [1,31] or concentrated on referrals to consultation services [13,29].…”
Section: Discussionmentioning
confidence: 99%